2023
DOI: 10.3390/plants12244123
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sustainable Exploitation of Bioactive Compounds in Pelargonium sp.: Beyond a Fragrant Plant

Sara Roman,
Catalina Voaides,
Narcisa Babeanu

Abstract: This review article aims to present an overview regarding the volatile compounds in different scented species of Pelargonium and their biological activities, immunomodulatory activity, cytotoxic activity, high larvicidal activity and ethnopharmacological uses. Although the Pelargonium genus includes many species, we focused only on the scented ones, with the potential to be used in different domains. Pelargonium essential oil showed great properties as antioxidant activity, antibacterial activity (against K. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…Current pharmacological and medical studies have shown that GEO can have broad-spectrum actions in the field of dermatology (Figure 3), with the following pharmacological actions: antiviral, anti-inflammatory, antimicrobial, oral cavity fresheners, astringent, healing, antifungal, tissue regeneration, pain relievers, antioxidants, and antitumor actions. These actions have a significant impact on the patient's quality of life [73].…”
Section: Geranium Essential Oilmentioning
confidence: 99%
See 3 more Smart Citations
“…Current pharmacological and medical studies have shown that GEO can have broad-spectrum actions in the field of dermatology (Figure 3), with the following pharmacological actions: antiviral, anti-inflammatory, antimicrobial, oral cavity fresheners, astringent, healing, antifungal, tissue regeneration, pain relievers, antioxidants, and antitumor actions. These actions have a significant impact on the patient's quality of life [73].…”
Section: Geranium Essential Oilmentioning
confidence: 99%
“…Following the examination by gas chromatography, increased concentrations of citronellol of major importance were found in GEO, and smaller quantities of α-pinene, limonene and β-pinene, and phytoconstituents were also present in FC, with high-level antibacterial and antifungal actions (Figure 4) [5,73]. GEO can be used in dermatology due to its increased potential in cleansing, odorizing, and purifying the skin, with multiple benefits for the treatment of acne and other dermatological conditions of microbial origin.…”
Section: Geranium Essential Oilmentioning
confidence: 99%
See 2 more Smart Citations